Sistem Informasi Jasa Reparasi Gadget Berbasis Website di Toko Light Service - Rizal Irfansyah Putra; Titus Kristanto; Fidi Wincoko Putro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Light Service Stores are shops that provide gadget repair services, such as Android cellphones, iPhones, Macbooks, selling gadget components, and so on. Activities at the Light Service Store begin when the customer comes to the counter regarding the problem with the gadget to be repaired, and then the customer delivers the gadget to the counter for repair. During the gadget repair process, customers can inquire about the progress of the gadget being repaired. After the gadget has been repaired, the admin informs the customer that the gadget has been repaired, and then the customer makes a payment. There are problems faced, namely that the way to manage customer orders is still conventional, so customers cannot monitor the progress of gadget repairs. Based on the problems faced by shop owners, a website-based gadget repair information system was created. The purpose of creating a gadget repair information system is to make it easier for customers to monitor gadget repair status and manage repair service orders. The method used in making the gadget repair information system is the Scrum method, where the Scrum method is more flexible if changes occur during the application development process and according to the wishes of the user because it gets regular feedback. In testing the website, the researcher used the User Experience Questionnaire (UEQ) to produce a pragmatic quality value of 2.0875, a hedonic quality value of 1.7125, and an overall value of 1.9, so it can be concluded that the application can be used by users and shop owners.